The Influence of CAR, FDR, NPF, and Profit Sharing Ratio on BCA Syariah's Financial Performance for the 2016-2022 Periods - Dina Christiana; Putri, Rizky Nur Ayuningtyas (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
The rapid development of the banking world at this time is one of the factors that makes daily financial transactions easier. One way to see how well PT is performing. BCA Syariah Bank is based on its financial reports, as the object to be studied, researchers will analyze BCA Syariah's quarterly financial reports obtained from the official OJK website. Financial performance can be seen from the size of ROA, while the size of ROA itself can be influenced by CAR, FDR, NPF and Profit Sharing Ratio. Therefore, the aim of this research is to determine the partial and simultaneous influence of CAR, FDR, NPF and Profit Sharing ratio on BCA Syariah's ROA for the 2016-2022 period. The samples in the research were all quarterly financial reports for the 2016-2022 period with a total of 28 samples and the sampling technique was purposive sampling. The analytical method used is multiple linear regression analysis with the help of the Eviews 10 program. The research results show that partially (1) CAR has a significant negatif effect on ROA, (2) FDR, NPF and Profit Sharing Ratio do not have a significant effect on ROA. Meanwhile, CAR, FDR, NPF and Profit Sharing Ratio simultaneously influence BCA Syariah's ROA for the 2016-2022 period.